Innate immune response to bacterial urinary tract infection sensitises high-threshold bladder afferents and recruits silent nociceptors. Issue 1 (January 2020) - Brierley, Stuart M.; Goh, Kelvin G.K.; Sullivan, Matthew J.; Moore, Kate H.; Ulett, Glen C.; Grundy, Luke
Abstract : Abstract: The bladder is innervated by primary afferent nerve fibres that detect bladder distension and, through projections into the spinal cord, provide sensory input to the central nervous system circuits regulating bladder sensation and function. Uropathogenic E. coli (UPEC) bacteria are the primary cause of urinary tract infection (UTI) in adults, inducing clinical symptoms characterised by exaggerated bladder sensation, including urgency, frequency, and pelvic pain. However, the mechanisms underlying UTI-induced modulation of bladder afferent function are yet to be explored. Here, we isolated supernatants from the bladders of female mice acutely infected with UPEC (strain CFT073), or those sham-treated with phosphate buffered saline. Supernatants were then applied into the bladder lumen of healthy donor mice, and multiunit bladder afferent nerve responses to distension measured ex-vivo. Supernatant constituents from UPEC or sham-treated mice were analysed using a mouse cytokine multiplex assay. Supernatants from UPEC-infected mice significantly enhanced bladder afferent firing to distension in the absence of changes in muscle compliance. Further evaluation revealed that UPEC supernatants exclusively sensitised high-threshold bladder mechanoreceptors to graded bladder distension and also recruited a population of "silent nociceptors" to become mechanosensitive, thereby amplifying bladder afferent responses to physiological stimuli. UPEC supernatants contained significantly elevated concentrations of a range of cytokines released from innate immune cells, including but not limited to TNF-α, IL-1β, IL-6, IL-17, IFN-gamma, and MCP-1. These data provide novel mechanistic insight into how UPEC-mediated UTI induces bladder hypersensitivity and the symptoms of frequency, urgency, and pelvic pain. Abstract : Supplemental Digital Content is Available in the Text.The innate immune response to E. coli -induced urinary tract infection sensitises "high-threshold" mechanosensitive bladder afferent neurons to initiate pelvic pain during bladder distension.